2021
DOI: 10.12659/ajcr.931116
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcemia and CYP24A1 Gene Mutation Diagnosed in the 2nd Trimester of a Twin Pregnancy: A Case Report

Abstract: Patient: Female, 33-year-old Final Diagnosis: Hypercalcemic crisis • pregnancy Symptoms: Hypercalcemia • hypertension • hypertensive crisis • pregnancy Medication: — Clinical Procedure: — Specialty: Genetics Objective: Rare disease Background: Loss-of-function mutations of the CYP24A1 gene cause a deficiency of the CYP24A1 enzyme, which is involved in the catabolism of 1,25-dihydroxyvitamin D3. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Conclusions on efficacies of these treatments cannot be made due to the observational nature of these limited data and the challenge to disentangle potential effects of specific drugs (a) from each other when used in combination, (b) from general treatment approaches such as stopping vitamin D supplement intake, and (c) from the natural course of the disease. In general, serum calcium levels were not significantly and consistently reduced or normalized after initiation of the above-described specific drug treatments except for some cases in which vitamin D supplement intake was stopped in parallel (e.g., case numbers 6 and 9 in Table 3) [19,21]. Of note, some authors concluded on the missing effect of their treatment such as in terms of glucocorticoids (case number 13 in Table 3) [24].…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Conclusions on efficacies of these treatments cannot be made due to the observational nature of these limited data and the challenge to disentangle potential effects of specific drugs (a) from each other when used in combination, (b) from general treatment approaches such as stopping vitamin D supplement intake, and (c) from the natural course of the disease. In general, serum calcium levels were not significantly and consistently reduced or normalized after initiation of the above-described specific drug treatments except for some cases in which vitamin D supplement intake was stopped in parallel (e.g., case numbers 6 and 9 in Table 3) [19,21]. Of note, some authors concluded on the missing effect of their treatment such as in terms of glucocorticoids (case number 13 in Table 3) [24].…”
Section: Literature Reviewmentioning
confidence: 97%
“…A literature review in PubMed using the search terms "CYP24A1" and "pregnancy" was performed on 13 April 2022 to identify articles presenting data on pregnant women with pathogenic CYP24A1 mutations causing hypercalcemia. Out of 97 articles, we identified 9 eligible manuscripts by this search strategy and by screening their reference lists, we retrieved two additional publications so that 11 articles were included in our work [15][16][17][18][19][20][21][22][23][24][25]. Overall, we retrieved 13 women with pathogenic CYP24A1 mutations who had reports on 29 pregnancies.…”
Section: Literature Reviewmentioning
confidence: 99%